Interpretasi Ayat Qawwamah pada Kepemimpinan Keluarga (Kajian Hermeneutika Atas Wacana Legislasi Hukum Keluarga Islam Indonesia) - Muttaqin Choiri (Proceedings of Annual Conference for Muslim Scholars, 2017)
One of the renewal method of Islamic family law is by rereading the Holy Qur’an translation, or reinterpretation, so that it can be got the new meaning of some meanings having existed previously. Hermeneutics in this case, is used to express the interpretation of the An-Nisa’ verse: 34 or it can be known with the qawwâmah verse, discussing about the authority of the man (husband) to the woman in the family, having consequences and particular special thing also.By doing this effort, in renewing Islamic family law in Indonesia also has sensitivity of the gender, in where the understanding of the leadership position in this qawwâmah verse is as a social responsibility, and the leadership description is as descriptive context to the descending the verse, as the effort of the forming a family of the sakiînah, mawaddah, wa rahmah, that always bases on Al-Qur’an and Sunnah.